Manifestasi Klinis Mata pada Infeksi Covid-19 - Dianti Sevina Salma Elmasri (CV. Jasa Sukses Abadi, 2020)
Coronavirus Disease 2019 (COVID-19) is a new kind of disease that has never been identified before in humans. The disease is caused by the novel severe acute respiratory syndrome-coronavirus-2 (Sars-CoV-2), which will make the person who is attacked have symptoms of pneumonia. Ocular transmission in the case of COVID-19 should not be ignored. Obtained data on a study conducted in China, positive patients with COVID-19 can have ocular manifestations, such as epiphora, conjunctival congion, chemosis, and these occur in patients with more severe systemic manifestations. Other studies also indicate the presence of clinical manifestations that meet the criteria of acute viral conjunctivitis. Ocular transmission can occur because when a pathogen in the eye, it is partially absorbed by the cornea and the conjunctiva and is largely flowed into the nasal cavity through the nasolacrimal tract and then transported to the lower part of the respiratory tract, including the nasopharynx and trachea, or swallowed into the gastrointestinal tract. This allows the pathogens about the eye to be carried up to the respiratory tract and the gastrointestinal tract.